Diet of lactating South American sea lions, as inferred from stable isotopes, influences pup growth - Drago, Massimiliano (2010)
Serum and blood cell δ13C and δ15N signals from 26 suckling pups of the South American sea lion from northern Patagonia were used as proxies of the composition of their mothers' diet to test the hypothesis that the foraging habits of the mother influence pup growth. Samples of primary producers and the female potential prey were analyzed to establish baseline isotopic values and to determine energy density. Pups were weighed to determine specific growth rate. Individual variability in female diet was large, probably as a consequence of dissimilarities in the foraging performance that depends on the individual's age, body size, and/or foraging skills. Growth of a pup was influenced by its mother's diet, as pups of females mostly relying on pelagic offshore prey were found to grow faster than those of females basing their diet on benthic coastal prey.